Evidence suggesting that virulence maps to the P1 region of the coxsackievirus B4 genome. - Ramsingh, A (1990)
A chimeric virus containing the P1 region of a virulent variant of coxsackievirus B4 and the P2 and P3 regions of a nonvirulent strain was constructed from cDNA clones. The chimeric virus induced pancreatitis with concurrent hypoglycemia similar to that observed in mice infected with the virulent variant.